Determinants of quality of life in Parkinson's disease: a perspective of novel clinical subtypes. Issue 11 (30th October 2021) - Fan, Yun; Zhang, Mengwei; Liang, Xiaoniu; Shen, Bo; Xu, Zhiheng; Li, Shiyu; Hu, Tianyu; Wu, Bin; Zhao, Jue; Sun, Yimin; Liu, Fengtao; Tang, Yilin; et al.
Abstract: Objective: New subtyping classification systems of Parkinson's disease (PD) have been proposed for phenotyping patients into three different subtypes: mild motor‐predominant (PD‐MMP), intermediate (PD‐IM) and diffuse malignant (PD‐DM). The quality of life (QoL) underlying the novel PD clinical subtypes is unknown. This study aimed explore the feasibility of the classification in Chinese PD patients and to investigate the potential heterogeneous determinants of QoL among the three subtypes. Methods: 298 PD patients were enrolled, including 129 PD‐MMP patients, 121 PD‐IM patients and 48 PD‐DM patients. All patients completed the QoL assessment, clinical evaluations and neuropsychological tests. Univariate linear analysis and multiple stepwise regression analysis were performed to identify determinants of QoL. Results: Compared to PD‐MMP patients, PD‐IM and PD‐DM patients had more impaired QoL. The Geriatric Depression Rating Scale (GDS) score, Non‐Motor Symptoms Questionnaire (NMSQ) score, Unified Parkinson's Disease Rating Scale part III (UPDRS‐III) score and Epworth Sleepiness Score (ESS) were independent contributors to QoL in PD‐MMP patients. The GDS score, ESS and sniffin' sticks screening 12 test score were independent contributors to QoL in PD‐IM patients. The GDS score and Mini Mental State Examination score were independent contributors to QoL in PD‐DM patients. Interpretation: The new novel subtyping classification is feasible for Chinese PD patients. Although depression was the most crucial determinant for QoL in PD‐MMP, PD‐IM and PD‐DM patients, the other contributors of QoL in the three subtypes were heterogeneous. These findings may prompt clinicians to target specific factors for improving QoL depending on PD subtypes.